Evaluasi Pengendalian Inflasi di Kota Bandar Lampung Tahun 2018 - Vivi Monica Sari; Bambang Utoyo; Novita Tresiana (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2021)
Inflation is one of the economic problems of a country including Indonesia. One of the efforts of the Indonesian government to control inflation is by coordinating with Bank Indonesia to establish an Inflation Control Team at the central and regional levels, through which the program is implemented to control inflation. The purpose of this research is to evaluate inflation control conducted by the Bandar Lampung City Government through the Bandar Lampung Regional Inflation Control Team in the foodstuffs group which is one of the contributing factors to high inflation in 2018. This research uses descriptive research method with qualitative approach, and uses data collection technique by interview, observation and documentation. Data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing, while for data validity techniques using observation and triangulation extension techniques. This research uses Karl Ludwig Bartelenfy's evaluation model of input, process, output, results, and impact evaluation. The results of this study concluded that in controlling the inflation of foodstuff groups the Regional Inflation Control Team through the food task force carried out various programs of activities, among others, monitoring, coaching, market inspection and monitoring market prices, as well as market operation or cheap markets. From the activities program can be seen how the development of market prices, minimizing the circulation og products that do not meet the standards, and the availability of foodstuff. Program of activities have iven quite good results, this can be seen from the trendline chart taht shows a decrease in the foodstuff. Although it has not been significantly due to constraints on the budget, it also has a good impact in addition to the decrease in the inflation index but also on increasing cooperation with new partners that is expected to help and facilitate efforts to control inflation in the future.